FRONT-END DEVELOPMENT OF WEB-BASED E-MAIL MANAGEMENT SYSTEM IN TELKOM ACCESS KEDATON BANDAR LAMPUNG - Meida Cahyo Untoro; Oktaviana Rinda Sari (UNIVERSITAS STEKOM, 2022)
The development of information has penetrated into the digital realm, by utilizing computer technology as an information technology tool in an organization or company will provide added value to the data processing process. The process of data processing in the form of incoming and outgoing letters at PT. Telkom Access is still done conventionally as well as manual archiving, with higher correspondence intensity and demands for speed and punctuality. In this study, we will develop a website-based e-mail management system display using the CodeIgniter3 framework and Bootstrap with the scrum methodology. It is hoped that by developing the appearance of the system, it can make it easier and more comfortable for users to use the system.